A slightly high-normal glucose level is associated with increased arterial stiffness in Japanese community-dwelling persons with pre-diabetes. (October 2013) - Kawamoto, Ryuichi; Tabara, Yasuharu; Kusunoki, Tomo; Abe, Masanori; Kohara, Katsuhiko; Miki, Tetsuro
Impaired fasting glucose (IFG) in diabetes is a risk factor for arterial stiffness and cardiovascular disease (CVD), but the impact of a slightly high-normal glucose level remains controversial. We investigated whether slightly high-normal fasting plasma glucose (FPG) was independently associated with arterial stiffness in non-diabetic community-dwelling persons. We recruited 114 men aged 69 ± 9 years (range 40–89) and 208 women aged 68 ± 7 years (range 36–84) during their annual health examination in a single community. Arterial stiffness was evaluated by the mean of the right and left brachial–ankle pulse wave velocity (ba-PWV). Age-adjusted ba-PWV increased significantly from the lowest to the highest FPG group ( p < 0.001). Multiple linear regression analyses for ba-PWV revealed that FPG levels (β=0.154, p < 0.001) were independently and significantly associated with ba-PWV. The multivariate-adjusted ba-PWV value of the high-normal glucose group (Group 3: 95–100 mg/dL) was significantly higher than that of the lowest normal glucose group (Group 1: 52–89 mg/dL) ( p =0.021), and the ba-PWV value in the IFG group (Group 4: 101–125 mg/dL) was significantly higher than those of the normal glucose groups (Group 1: <90 mg/dL; Group 2: 90–94 mg/dL) ( p <0.001 and p =0.009, respectively). Slightly high-normal glucose levels were associated with arterial stiffness in Japanese community-dwelling persons.